Making peace with disaster: A study of earthquake disaster communication through manuscripts and oral traditions - Fakhriati Fakhriati; Daratullaila Nasri; Mu'jizah Mu'jizah; Yeni Mulyani Supriatin; Asep Supriadi; Musfeptial Musfeptial; Kustini Kustini (Progress in Disaster Science, 2023)
Effective disaster communication enables communities to take action in preparing for and reducing the risk of disasters. While there are modern technologies for disaster communication, indigenous ways were proven to be effective in saving local communities from numerous recurring natural disasters in Indonesia. This study aims to explore the communication patterns of local communities in preventing, mitigating, and recovering from disasters, particularly earthquakes. Employing philological, historical, and anthropological approaches, this study investigates disaster communication based on local knowledge and practices in the three areas most impacted by earthquakes: Sumatra, Jawa, and Bali. Examination of local ancient manuscripts, interviews with local leaders, and direct observations on local practices were conducted to obtain comprehensive data. This study found that local communities in Indonesia used what is called triangular communication, i.e., communication of human-to-God, human-to-human, and human-to-nature. This pattern has long been internalized among local communities and strengthened in the face of disasters. Traditional disaster communication works effectively for local people in areas that are especially inaccessible for rescue or aid from the local government. This study suggests that local knowledge is a culturally responsive and effective tool for disaster communication, as it originates from local history and tradition.